Circular economy applied to wastewater treatment plants: an analysis of the energy generation potential at the Passos/MG WWTP - Dias, Álvaro José; Meireles, Eduardo; Guimarães, Ester Feche; Rosa, Jean Lucas; Balliano, Tatiane Luciano (National Journal of City Management, 2024)
The aim of this study was to analyze the pruojects carried out by company Sabesp in the state of São Paulo, especially in the municipality of Franca/SP, developed in partnership with the Fraunhofer Institute, which consists of reusing the sludge generated at its plants, transforming it into fuel (biogas) and fertilizer for agricultural recycling. In addition, the WWTP of the city of Passos/MG will also be analyzed, so that the main points and differences can be listed and analyzed, seeking to replicate the fundamental processes of Sabesp's projects at the WWTP in the municipality of Minas Gerais. The methodology used was the case study, where quantitative and qualitative data were collected from plants, which were compared and supported by a bibliographic review in order to list replicable processes. In this sense, it is expected that the work will contribute to the dissemination of Circular Economy concepts and assist in the sustainable development of the region, serving as a reference for the replication of good sanitation practices.
Keywords: Sanitation; Solid waste; Sustainability; Development